1998
DOI: 10.1128/mcb.18.1.178
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mitochondrial Inner Membrane Translocase Complex: the Tim23p Hydrophobic Domain Interacts with Tim17p but Not with Other Tim23p Molecules

Abstract: Tim23p is a mitochondrial inner membrane protein essential for the import of proteins from the cytosol. Tim23p contains an amino-terminal hydrophilic segment and a carboxyl-terminal hydrophobic domain (Tim23Cp). To study the functions and interactions of the two parts of Tim23p separately, we constructed tim23N, encoding only the hydrophilic region of Tim23p, and tim23C, encoding only the hydrophobic domain of Tim23p. Only the Tim23C protein is imported into mitochondria, indicating that the mitochondrial targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 76 publications
2
54
0
2
Order By: Relevance
“…When HA-Net2p-containing mitochondria were incubated with trypsin, all of the HA-Net2 protein was digested, similarly to OM45p, a mitochondrial outer membrane protein that faces the cytosol ( Figure 5D; Yaffe et al, 1989). In contrast, Tim23p, which contains a proteasesensitive domain that faces the intermembrane space (Ryan et al, 1998), was protected from digestion by the outer membrane. These results indicated that Net2p associates with the cytosolic face of the mitochondrial outer membrane.…”
Section: Net2p Is Located In Punctate Structures On the Mitochondrialmentioning
confidence: 99%
“…When HA-Net2p-containing mitochondria were incubated with trypsin, all of the HA-Net2 protein was digested, similarly to OM45p, a mitochondrial outer membrane protein that faces the cytosol ( Figure 5D; Yaffe et al, 1989). In contrast, Tim23p, which contains a proteasesensitive domain that faces the intermembrane space (Ryan et al, 1998), was protected from digestion by the outer membrane. These results indicated that Net2p associates with the cytosolic face of the mitochondrial outer membrane.…”
Section: Net2p Is Located In Punctate Structures On the Mitochondrialmentioning
confidence: 99%
“…Tim23 consists of two domains, a C-terminal hydrophobic domain located in the inner membrane and an N-terminal domain that is exposed to the intermembrane space and binds mitochondrial presequences 13,17,21,22,24 (Fig. 6a).…”
Section: Channel Formation By the C-terminal Domain Of Tim23mentioning
confidence: 99%
“…However, proteins that lack a presequence and use internal targeting signals instead, like many carrier proteins of the inner membrane, undergo a distinct import pathway (7)(8)(9)(10). This involves not only the TOM complex in the outer membrane (7,11) but the insertion-specific TIM22 complex in the inner membrane (8,(12)(13)(14)(15). Quite uniquely, the carrier import pathway also depends on the function of two soluble 70-kDa complexes made of Tim9 and Tim10 (the TIM10 complex) (16 -20) or Tim8 and Tim13 (21,22).…”
mentioning
confidence: 99%